DOES FAMILY SUPPORT AND WORK PERFORMANCE PREDICT WORK–LIFE BALANCE AMONG LOW-INCOME GROUP (B40) ELDERLY INFORMAL CAREGIVERS IN MALAYSIA? - Abdul Rahim, Siti Nor Izahh; Ismail, Shafinar; Krishnan, Ramesh (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2026)
This study examines how family support and work performance affect the work–life balance of low-income group (B40) elderly informal caregivers in Malaysia, a group that faces dual responsibilities of employment and caregiving. Despite growing attention to caregiver well-being, empirical research has focused primarily on how these factors influence balance within low-income caregiving households. The study utilises survey data collected from 204 respondents from B40 workers who provide unpaid care for older family members across several Malaysian states. Partial Least Squares Structural Equation Modelling (PLS-SEM) was employed to evaluate the direct effects of family support and work performance on work–life balance, guided by Work–Family Conflict Theory. The results show that both predictors significantly enhance work–life balance, with work performance emerging as the more substantial determinant. Caregivers who perform well at work tend to experience lower strain and fewer work–family interferences. Family support can help overcome caregiving burdens and better align home and work responsibilities. These findings have meaningful implications for organizations and policymakers, enabling them to improve the well-being of B40 informal caregivers and strengthen overall work–life balance.